The change in the role of management accounting in a public sector organization: an institutional interpretation / Sujatha Perera - Perera, Sujatha (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2007)
Public sector organizations in Australia have been undergoing major changes and reforms since the 1980s. The existing literature on organizational change in the public sector suggests that such reforms have important implications for management accounting practices in public sector organizations. Informed by two bodies of literature, namely organizational and accounting change literature and institutional literature, this paper examines: (i) the factors that generated or stimulated change in the role of management accounting in a government trading enterprise over the period from the mid 1980s to the mid 1990s; and (ii) the nature and form of changes that occurred in the role of management accounting of the case study organization during the period under investigation.